Business Research Methods and Methodology in Practice: Understanding the Advanced SmartPls Path Models in Structural Equation Modeling - Adam, Abdul-Kahar (Journal of Business Management and Economic Development, 2026)
The purpose of this paper is to advocate the use of SmartPLS in scientific research by adopting business methodologies and variables, namely discipline, good governance, and probity. The aim is to present the findings and data analysis using SmartPLS 4.1.1.4 components. The study population comprised 187 students in the Level 300 HRM class, and a sample size of 126 was determined using Krejcie and Morgan's (1970) formula. The results were based on factor loadings, discriminant validity, composite reliability, and collinearity statistics. The findings indicate that the outer loadings with appropriate p-values indicate that the majority of the factors are significantly loaded. But it is not a surprise that 1a. <- Good Governance, 1c. <- Good Governance, and 2a. <- Control of Corruption is not significantly loaded because it means that there are certain effects that affect Good Governance and the control of corruption. Responsibility and Discipline failed the discriminant validity test, indicating that the Follow Responsibility factor and the Discipline variable were not in agreement with the measurement, implying that certain factors affect this variable-factor relationship. SmartPLS 4.1.1.4 App was used to run the data.